Comparison of the Effectiveness of Mentalization-Based Therapy and Emotion Efficacy-Based Therapy on Cognitive Insight and Distress Tolerance in Adolescents with Generalized Anxiety Symptoms - Haghshenas, Fariba; Rava, Bahareh; Hemmati, Razieh; Sanagouye Moharer , Gholamreza; Fardin, Mohammadali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective:  The present study aimed to compare the effectiveness of Mentalization-Based Therapy and Emotion Efficacy-Based Therapy on cognitive insight and distress tolerance among adolescents with generalized anxiety symptoms.Methods and Materials: This study was applied in terms of purpose and quasi-experimental in terms of methodology, utilizing a pretest–posttest design with two experimental groups and one control group. The statistical population consisted of male and female adolescents with generalized anxiety symptoms in Shiraz during 2025. The sample included 45 adolescents selected through convenience sampling and randomly assigned into three groups of 15 participants each. The first experimental group received Mentalization-Based Therapy, the second experimental group received Emotion Efficacy-Based Therapy, and the control group received no intervention. Data collection instruments included the Beck Cognitive Insight Scale, the Distress Tolerance Scale, and the Generalized Anxiety Disorder Questionnaire (GAD-7). The interventions were implemented over eight weekly 90-minute sessions. Data were analyzed using descriptive statistics and multivariate analysis of covariance (MANCOVA) in IBM SPSS Statistics.Findings: The results indicated significant differences between the experimental and control groups in cognitive insight and distress tolerance (Wilks’ Lambda = 0.266, F₄,₇₈ = 18.293, p < .01). Univariate covariance analysis demonstrated that both Mentalization-Based Therapy and Emotion Efficacy-Based Therapy significantly improved cognitive insight (F₂,₄₀ = 20.593, p < .001, η² = 0.507) and distress tolerance (F₂,₄₀ = 17.987, p < .001, η² = 0.474) compared to the control group. Bonferroni post hoc comparisons further revealed that Mentalization-Based Therapy was significantly more effective than Emotion Efficacy-Based Therapy in enhancing cognitive insight (p < .01), whereas Emotion Efficacy-Based Therapy demonstrated greater effectiveness in improving distress tolerance (p < .05).Conclusion: These results emphasize the importance of selecting therapeutic interventions based on the primary psychological needs and treatment goals of adolescents with generalized anxiety symptoms.